Function and genetics of dystrophin and dystrophin-related proteins in muscle. - Blake, D; Weir, A; Newey, S; Davies, K (2002)
The X-linked muscle-wasting disease Duchenne muscular dystrophy is caused by mutations in the gene encoding dystrophin. There is currently no effective treatment for the disease; however, the complex molecular pathology of this disorder is now being unravelled. Dystrophin is located at the muscle sarcolemma in a membrane-spanning protein complex that connects the cytoskeleton to the basal lamina. Mutations in many components of the dystrophin protein complex cause other forms of autosomally inherited muscular dystrophy, indicating the importance of this complex in normal muscle function. Although the precise function of dystrophin is unknown, the lack of protein causes membrane destabilization and the activation of multiple pathophysiological processes, many of which converge on alterations in intracellular calcium handling. Dystrophin is also the prototype of a family of dystrophin-related proteins, many of which are found in muscle. This family includes utrophin and alpha-dystrobrevin, which are involved in the maintenance of the neuromuscular junction architecture and in muscle homeostasis. New insights into the pathophysiology of dystrophic muscle, the identification of compensating proteins, and the discovery of new binding partners are paving the way for novel therapeutic strategies to treat this fatal muscle disease. This review discusses the role of the dystrophin complex and protein family in muscle and describes the physiological processes that are affected in Duchenne muscular dystrophy.